The Role of Entrepreneurship in Promoting Economic Development: A Field Study on Some of Pilot Projects in Jeddah - Al-Yazidi, Rizqallah Abdullah (The Arab Journal of Administration, 2024)
This study aimed at identifying the role of entrepreneurship in promoting economic development, identifying the role of entrepreneurial projects in reducing the problem of unemployment and revealing the difficulties facing entrepreneurship in the Kingdom of Saudi Arabia, the study followed the descriptive analytical approach, and the questionnaire was used to obtain the analysis data, while the study sample consisted of managers and owners of entrepreneurial projects in Jeddah, and the sample consisted of (40) managers and owners of entrepreneurial projects, the results of the study showed that the entrepreneurial behavior is available to a high degree, and that the leaders of the entrepreneurs have a desire to achieve and excel in their work, they also have new ideas related to their business that they initiate, the study also showed that entrepreneurship enhancers are available to a moderate degree and that entrepreneurs receive support and encouragement from working individuals, entrepreneurs are also interested in training and education to develop the entrepreneurial spirit of workers. The study also showed the most important difficulties facing entrepreneurs, which are the difficulty of providing a guarantor to obtain financing, and the insufficient financing in some projects, the study recommended that the state should work to simplify the procedures related to the implementation of pioneering projects. It also recommended that the authorities concerned with developing pilot projects should work to increase interest in sponsoring creators and innovators and provide them with incentives, it is also necessary to work on finding mechanisms to provide capital and support to entrepreneurs, and to support and encourage entrepreneurship in order to find successful entrepreneurial projects that contribute to expanding job opportunities and contributing to reducing unemployment rates in the Kingdom of Saudi Arabia.